2018
DOI: 10.1155/2018/8293452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TGF-Beta 2 and VEGFα Gene Expression Levels in Epiretinal Membranes and Internal Limiting Membranes in the Course of Retinal Detachments, Proliferative Diabetic Retinopathy, Macular Holes, and Idiopathic Epiretinal Membranes

Abstract: Purpose To evaluate the expression profiles of the VEGFα and TGFβ in the ERMs and ILMs in retinal disorders. Methods In this nonrandomized prospective study, 75 patients (34 females and 41 males) referred to pars plana vitrectomy (PPV) due to different retinal diseases were enrolled to the study. The samples of ERMs and ILMs collected during PPV were immediately put in TRIzol® Reagent (Life Technologies, USA) and stored at −70°C until RNA extraction. Gene expression analysis was done with TaqMan® Gene Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…A bioinformatic approach guided the identification and in vitro validation of alternative target genes of miRNAs, dysregulated after inhibition of HIF-1α degradation. We analyzed the expression of genes of the TGFβ (Transforming growth factor beta) signaling pathway, which is an emerging target in DR ( Li et al., 2018 ; Stafiej et al., 2018 ) and was found to be one of top pathways modulated by HypoxamiRs target genes ( Gupta et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatic approach guided the identification and in vitro validation of alternative target genes of miRNAs, dysregulated after inhibition of HIF-1α degradation. We analyzed the expression of genes of the TGFβ (Transforming growth factor beta) signaling pathway, which is an emerging target in DR ( Li et al., 2018 ; Stafiej et al., 2018 ) and was found to be one of top pathways modulated by HypoxamiRs target genes ( Gupta et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the presence of VEGF receptors in ERM-forming cells was demonstrated. This suggests that VEGF acts as a growth factor for ERMforming cells (34,35).…”
Section: Cytokine or Molecule Descriptionmentioning
confidence: 99%
“…TGF-b is a family of cytokines that exhibit pleiotropic effects on tissues. These cytokines are involved in the control of the proliferation and migration of endothelial cells (34,42). Within the ERM, this cytokine is responsible for the differentiation of cells into fibroblast-like cells -responsible mainly for the production of ERM-building proteins (43).…”
Section: Transforming Growth Factors-b (Tgf-b)mentioning
confidence: 99%
“…Therefore, we veri ed the inhibitory effect of artesunate on EMT in PVR in vitro. TGF-β2 is abundant in vitreous humor of pvr patients, and its concentration is signi cantly related to the severity of PVR [17,18], in addition, it is the main promoter of PVR diseasesPrevious studies have shown that TGF-β2 intervention can induce emt transformation of RPE cells, and transformed RPE cells play an important role in excessive healing of pvr diseasesIn [19,20].In tumor cells, the combination of TGF-β and its receptor is out of control,Activation of several downstream pathways, including Smad, Ras and MAP kinases, PI3k/ Akt and so on, leads to cell dysfunction [21,22,23].Smads family proteins play a key role, and different Smad proteins can mediate the signal transduction of different TGF-β family members [24,25].Smad3 is a key signal transduction intermediate downstream of TGF-β2 activin receptor, and platelet-derived growth factor receptor can be induced by TGF-β signal.Furthermore, it can promote the EMT process of RPE cells, and tissue brosis and tissue contraction also depend on the activation of TGF-β/smad pathway [26,27,28].Studies have shown that after retinal detachment and traumatic rupture, pigment epithelial cells leave their normal positions, enter vitreous cavity and subretinal space, and autocrine TGF-β activates samd signaling pathway, thus promoting emt transformation of RPE cells [29].Through experiments,We found that in clinical vitreous samples, the expression of samd in class B and class C PVR samples was up-regulated compared with that in control group and class A PVR samples, and the content of activated smad expression also increased, thus further verifying the role of smad signaling pathway in the occurrence and development of PVRCompared with the control group, artesunate group can reduce the content of TGF-β2 secreted by ARPE-19 cells,Thereby reducing the activation degree of TGF-β/smad pathwayIn vitro cells induced by TGF-β, smad signaling pathway and phosphorylated smad increased, while samd3 and phosphorylated smad3 decreased after art treatmentIn animal experiments, we found that after injecting artesunate into vitreous cavity while modeling, the degree of vitreous opacity was reduced compared with the control group, and no retinal membrane was formed.The expression levels of cytoskeletal proteins VIM,smad3 and p-smad3 were lower than those of the control group.…”
mentioning
confidence: 99%